Comparative Dynamics of The Efficiency of Antithrombotic Prophylaxis Before Delivery In Pregnant Women With Different Forms of Antiphospholipid Synrome - Gurbanova, J.F.; Guliyeva, M.A. (Journal of Medical Biomedical and Applied Sciences, 2018)
Objectives: The aim of this study was the assessment of effectiveness of antithrombotic prophylaxis in pregnant women with different form of APS. Methods of study: For the assesment of condition and effectiveness of treatment of pregnants, the investigations were carried out in 92 women. In various periods of pregnancy were determined non-active thrombin-antithrombin III (TAT) complex, protrombin fragments (F1+2), D-dimer et c. Results and conclusions: Long-term antithrombotic prophylaxis with low-molecular heparins allows to decrease the level of thrombophilic markers in pregnant women with different forms of APS. Monotherapy with low-molecular heparins in women allows to normalize the level of thrombofilic markers and effectively prevents thrombosis.